Características de los coronavirus, origen del SARS-CoV-2, características estructurales, proteínas y factores de virulencia, variantes genéticas - Isler I., Dayanne; Palma P., Valeria (Revista Hospital Clínico Universidad de Chile, 2021)
Coronaviruses (CoVs) were identified in 1937, they were considered innocuous viruses until the appearance of three highly pathogenic variants, SARS-CoV, MERS-CoV and SARS-CoV-2 causing the current pandemic of Covid-19, so far it is known that its origin is zoonotic, the main reservoir could be bats considering the high homology of CoVs that inhabit this species. Its transmissibility is much higher than that of previous CoVs, possibly in the process of natural selection; it has acquired some or all the mutations necessary for a much more efficient transmission in our species. This condition is specifically attributed to unique characteristics of the SARS-CoV-2 Spike protein that allow it greater affinity and therefore greater infectivity by binding to the angiotensin receptor 2 (ACE-2) present in the host cells. Since the Covid-19 outbreak began at the end of 2019, more than 1,500 mutations have been detected throughout the SARS-CoV-2 genome, however the most significant are those that occur near or in the receptor binding domain (RBD) that could provide variations between 4x to 100x greater infectivity, such is the case of the new variants identified in the United Kingdom, South Africa, Brazil and Japan that force us to take extreme preventive measures and continue research to elucidate strategies to combat the current crisis.